Pembelajaran Bahasa Arab pada Pesantren Salaf dan Modern di Madura: Metodologi dan Strategi - Qumaruzzaman, Qumaruzzaman (Qismul Arab: Journal of Arabic Education, 2024)
Islamic boarding schools are divided into two types: salaf and modern. Both integrate Arabic language learning tailored to their respective focuses and objectives. This study explores the differences in Arabic learning methods and strategies between salaf and modern boarding schools using a descriptive qualitative approach, with data collected through observation and interviews. Findings reveal that salaf boarding schools prioritize maharoh qiro’ah (reading skills) to enhance understanding of Arabic texts, particularly classical Islamic sources such as al-kitab and as-sunnah, employing methods like grammar analysis (qowa’id) and translation. Conversely, modern boarding schools focus on maharoh kalam (speaking skills) to develop Arabic as a communication tool, utilizing the direct method (mubasyaroh) and strategies such as displaying vocabulary around dormitory spaces. These distinctions highlight the contextual adaptability of Arabic teaching in achieving educational goals aligned with each school's vision.